Ultrathin metal–organic framework nanosheets as building blocks of lamellar nanofilms for ultrafast molecular sieving. Issue 47 (23rd November 2022) - Wang, Guitu; Lu, Jingyu; Fang, Chuanjie; Fang, Wenzhang; Peng, Xinsheng; Zeng, Hongbo; Zhu, Liping
Abstract : Ultrathin, smooth, and square MOF nanosheets were synthesized. Such morphology facilitated the well-ordered intrinsic pore structure of MOFs to become building units of a molecular sieving nanofilm with both high permeance and rejection. Abstract : Metal–organic framework (MOF) nanosheets have significant potential applications including separation, catalysis, and sensors. However, the on-demand design with tunable thickness and morphology remains a great challenge, leading to difficulties in modulating their hierarchical assembly for the preparation of macroscopic films. Herein, we report the successful synthesis of smooth and ultrathin MOF (Cu-TCPP (TCPP = 4, 4, 4, 4-(porphine-5, 10, 15, 20-tetrayl)tetrakis(benzoic acid))) nanosheets used in lamellar nanofilms for the rejection of organic molecules from water. Dopamine hydrochloride (DA-HCl) is used as an adjuvant in the synthesis. Facilitated by a HCl acid environment and DA competitive coordination, the normal and lateral growths of Cu-TCPP nanosheets are modulated to achieve the desired thickness and morphology. DA-HCl can be also easily removed from the nanosheets without affecting their physicochemical properties. The as-synthesized nanosheets are utilized as nanofilm building blocks in which they are stacked into ordered bricks. The obtained membrane displays an ultrahigh water permeance of 2540 L m −2 h −1 bar −1, which is two orders of magnitude higher than the currently reported polymer membranes, while it does not sacrifice the solute rejection as completely determined by the intrinsic pore size of the nanosheets ( i.e., 98.8% for molecules larger than 1.3 nm). This work provides a novel and facile strategy to tailor the morphology of the MOF nanosheets for maximizing their functionalities and structure superiority in many engineering applications.